Pengaruh Kebiasaan Konsumsi Sayur, Buah dan Perokok Pasif terhadap Kapasitas Antioksidan Total Ibu Hamil - Nadimin, Nadimin (Media Kesehatan Masyarakat Indonesia, 2018)
The availability of antioxidants during pregnancy were decreases with increasing of gestational age and influenced by environmental factors such as exposure to cigarette smoke and consumption habits of vegetables and fruits. A cross sectional study with pregnant mothers (20-26 months pregnant) non-anemia as many as 70 people selected by purposive sampling. Total Antioxidant Capacity (KAT) was measured using Elisa method (enzyme-liked immunosorbent assay), vegetable and fruit consumption habits collected with Food Frequency Questionaire (FFQ) and smoking habits using interviews. The results showed around 37,1% of pregnant women were passive smokers and rarely consume vegetables and fruits (>60,0%). The mean KAT of pregnant women reached 2,73±1,48 mmol/l. KAT of passive smokers are significantly lower than non-passive smokers (p=0,038). In General pregnant women who often consume vegetables and fruits have a higher KAT. However, a higher KAT was significantly found in pregnant women who frequently consumed green mustard greens (p=0,049), green bean leaves (p=0,002), apples (p=0,007) and papaya (p=0,029). Exposure to cigarette smoke and less consumption of vegetables and fruits have lower KAT in pregnant women. Pregnant women should increase consumption of vegetables and fruits and avoid exposure to cigarette smoke.